Population Dynamics of Silver barb (Barbonymus gonionotus) in Tempe Lake Waters, Wajo Regency, South Sulawesi - Najamuddin; Rizka Awalia Sukarman; Faisal Amir (Hasanuddin University, 2024)
Silver barb (Barbonymus gonionotus) is a catch that is commonly found in the waters of Tempe Lake, Wajo Regency, South Sulawesi. Catching Silver barb (Barbonymus gonionotus) in the waters of Tempe Lake uses several types of fishing gear, including gill nets or lanra' (gill nets) with mesh sizes of 4, 4.5, 5, 6.5, 7, and 9 cm, dragon traps or ja'ba, traps, and lift nets. The purpose of this study is to analyze aspects of the population dynamics of Silver barb (Barbonymus gonionotus), which includes age group, growth, mortality, exploitation rate, and yield in a recruitment, and to analyze the catch of Silver barb (Barbonymus gonionotus) caught using gill nets, dragon traps, and lift nets. This research was conducted over two months, in November and December 2021. Stratified random sampling was used to select the participants. The fish were grouped into small, medium, and large sizes, and fish were randomly selected from each age group. The total sample obtained was 1600 tails with a total length range of 10-33 cm TL and an average length of 19.8 cm TL. The results of the analysis obtained two age groups: the first was in the length range of 10-18 cm, and the second was in the length range of 18-33 cm. Fish asymptote length (L∞) was 45 cm with a coefficient value (K) of 0.5 in a year, and fish age at length was zero (t0) = -0.2919 years. Natural mortality (M) was 1.05 per year, fishing mortality (F) was 2.19 per year, and total mortality (Z) was 3.24 per year. The exploitation rate value was 0.68, which exceeded the optimum exploitation rate (0.50). The value of yield in recruitment (Y/R') was 0.0166 g/recruitment, and the recruitment process was not normal.